Implications of the political character of education to the management of public schools (Educação e Pesquisa, 2002)
Starting from a broad conception of politics - transcending the mere struggle for power, and identifying politics with a human-social practice that has the purpose of making possible the living together of groups and people - the article elaborates an equally broad concept of democracy that, not being restricted to its parliamentary or electoral meaning, is understood as a social practice that builds the free and peaceful coexistence of individuals and groups that assert themselves as historical agents. Taken then as a historical-cultural actualization through which takes place the construction of the historical man through the acquisition of culture, education has its political dimension highlighted precisely because of this ability to endow the human being with their historical and plural condition, due to which they necessarily have to live with other individuals and groups. By analyzing the dialogic and reinforcing character of the subjectivity of the educated, through which the authentic education must take place in order to be coherent with its function of builder of the historical man, the work seeks to bring forward the nature of the education process not just as political practice but also as an intrinsically democratic practice. Within this framework the article considers the implications of this political and democratic condition to the quality of teaching, to the school management practice, and to the studies in school management.